The Organizational Culture and Innovation of Enterprises in the Era of the Fourth Industrial Revolution - Protasiewicz Anna; Zalesko Elzbieta (Studies in Logic, Grammar and Rhetoric)
The fourth industrial revolution, characterized by the development of advanced technologies such as artificial intelligence, the Internet of Things and automation, is radically changing the context of functioning of modern enterprises. In this environment, innovation is a key element of competitive advantage, and organizational culture is one of the fundamental factors enabling effective implementation of innovations. The aim of this article is to analyze the role of organizational culture as a catalyst for innovation in enterprises in the era of Industry 4.0. The paper discusses the basic elements of organizational culture, such as openness to change, cooperation between teams and organizational flexibility, which are of key importance in innovation processes. On this basis, conclusions are formulated regarding the impact of organizational culture on the ability of enterprises to compete and develop in a dynamically changing economic environment. The study has a theoretical and empirical character. For the research, the authors used the descriptive method with elements of statistical data analysis. The analysis was based on reports of such institutions as the World Economic Forum, McKinsey and secondary data regarding Polish enterprises.